Simulation and Performance Analysis of Discrete Load Controller for Micro-Hydropower Plant - Guruwacharya, Nischal; Shakya, Shree Raj (KEC Journal of Science and Engineering, 2023)
Electronic load controller (ELC) has been an in-dispensary part of governor free Micro hydro plant for frequency control for a long period of time. Conventional ELC consists of thyristor-controlled dump load system; in which firing angle regulates the amount of power to be fed into dump load. Such ELC units suffer many drawbacks, including injection to current harmonics, drawing high reactive current from the source. This study tries to address these issues by introducing a Discrete Load Controller (DLC). DLC controls the load by controlling the number of resistors to keep it ON or OFF without chopping source voltage. The system layout and control scheme are developed in Matlab® Simulink environment and different disturbance are introduced for dynamic response. The result shows that the DLC functions well, by generating less harmonics and consumption of reactive power; which otherwise are to be supplied by the generator itself. Further the DLC is also capable of regulating frequency at designated value in spite of all loading condition. Also, the result obtained from simulation is validated experimentally.